The Relationship Among Foreign Direct Investment, Inflation Rate, Unemployment rate, and Exchange Rate to Economic Growth in Indonesia - Irsania, Dea Vibby; Noveria, Ana (Journal of Business and Management, 2014)
The main theme of this project is economic growth and focus on finding the relationship among foreign direct investment, inflation rate, unemployment rate, and exchange rate toward the economic growth in Indonesia based on the multiple linear regression analysis. The result represents that FDI, inflation rate, unemployment rate, and exchange rate has a significant influence towards the economic growth. The two of them which are exchange rate and inflation rate show a significant influence toward the economic growth. Thus, when the exchange rate and inflation rate increase, the economic growth will be decrease. Meanwhile, the rest of them which are unemployment rate and FDI also have a significant influence toward the economic growth. If FDI and unemployment rate increase, then Indonesia’s economic growth will also increase. Indonesia as a developing country shows an increase in the influence of Foreign Direct Investment toward economic growth and allow it to continue to rise in the future, but for now all of the macroeconomics factors that observed in this research have a significant influence toward Indonesia’s economic growth.Keywords: Foreign Direct Investment, inflation rate, exchange rate, unemployment rate, economic growth, relationship, multiple linear regression analysis